Effects of knowledge, attitudes, and practices of poultry handlers on the prevalence of Campylobacter along the poultry production chain in peninsular Malaysia - Abdul Rahiman, Ummu Afiqah; Azuddin, Siti Nur Amirah; Abdul Mutalib, Noor Azira; Sanny, Maimunah; Mahmud @ Ab Rashid, Nor Khaizura; Nordin, Noordiana (UPM Press, 2023)
The present work aimed to identify the effects of knowledge, attitudes, and practices (KAP) of poultry handlers on the prevalence of Campylobacter along the poultry production chain in Peninsular Malaysia. A total of 1230 microbiological samples were collected from five companies in different Malaysian states. The sampling points involved the entire poultry supply chain from the farm to the retailer. The collected samples were subjected to bacteriological isolation and morphological identification for microbiological analyses. All Campylobacter-positive samples were further confirmed with molecular identification by using a polymerase chain reaction. Campylobacter prevalence in poultry farms, processing plants, and retailers were identified. For the KAP survey, 300 respondents answered a questionnaire evaluating their levels of KAP regarding food safety while handling live birds and subsequently poultry products after slaughtering. Overall, the mean KAP scores of the workers at farms, processing plants, and retail outlets were assessed. The survey data indicated that even though the overall KAP levels of the poultry workers were excellent, the bacterial prevalence of Campylobacter was still high. In conclusion, the KAP of poultry handlers had insignificant effects on the prevalence of Campylobacter along the poultry production chain in Peninsular Malaysia.